Dengue prevention program of barangay Mintal Health Committee a communication plan - Rinos, Ella Bernadette J.
The thesis production, Dengue Prevention Program of Barangay Mintal Health Committee: a communication plan, aims to intensify the program by producing a prototype communication plan that will cater to the needs of the general public of Barangay Mintal. The research part concentrates on knowing the existing communication strategies of Barangay Mintal committee in its Dengue Prevention Program. While Aristotle?s Rhetoric served as a guide in conducting an audience and SWOT (Strengths-Weaknesses-Opportunities-Threats) analysis, Azjen?s Theory of Planned Behavior and 6-Step marketing Wheel was employed in the production process. Results showed that the existing communication strategies of the committee were generally reactive. Moreover, there was minimal situational and audience research conducted; the committee does not also employ evaluation techniques. On the other hand, findings show the essentiality of removing control beliefs and attitudes in the process of motivating the target audience in materializing the suggested behavior. The outcome of the audiences and SWOT analysis aided the researcher to identify strategies to amplify the program. The prototype design of the communication plan centers on enabling a proactive communication efforts. Specifically, the design aims not only to raise more awareness about Dengue virus but also to encourage mothers and other family members to give importance environmental sanitation. More importantly, potential partner-stakeholders, strategic places, communication tool mix, and evaluation techniques were also identified in the process.